Pulmonary sarcoidosis in a preschool patient. Issue 12 (26th June 2015) - Shanthikumar, Shivanthan; Harrison, Jo
Summary: Sarcoidosis is a rare disease, especially in the preschool age group where it usually presents with eye, joint, and skin involvement sparing the lungs. Multiple treatment regimes have been described with oral prednisolone being the usual first line treatment. We describe a case of a 4‐year‐old boy presenting with pulmonary sarcoidosis with no other organ involvement. The child was successfully managed with pulse intravenous methylprednisolone followed by oral prednisolone and has had a good outcome. This case reports a rare presentation of preschool sarcoidosis as well as the novel and successful use of pulse methylprednisolone in paediatric pulmonary sarcoidosis.Pediatr Pulmonol. 2015; 50:E41–E43. © 2015 Wiley Periodicals, Inc.